SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GEDUNG PERNIKAHAN PADA WILAYAH BANDAR LAMPUNG MENGGUNAKAN METODE TOPSIS - Dellys Okta Wibowo; Adhie Thyo Priandika (Universitas Teknokrat Indonesia, 2021)
The development of the business world in Indonesia has shown a creative direction. This is proven by the proliferation of various forms of business entities engaged in goods and services, both small and large scale. One of them is wedding hall rental services. The wedding hall has become a necessity for potential partners due to limited land for holding weddings at home or around the house, for potential partners to get a wedding hall is very difficult because prospective clients have to go to the building one by one to choose the building that suits them. However, the decision to choose a wedding hall is not an easy one, there are many factors that must be considered, including the time and budget that the bride and groom have. Making a decision that combines quantitative and qualitative elements can be assisted by a decision support system (DSS), which according to its understanding, DSS is an interactive computer-based system, which helps decision makers to use data and various models to solve unstructured problems. So the authors decided to use the TOPSIS method in Decision Supporting System for Choosing Wedding Hall in Bandar Lampung Region.